Urgensi Mendengarkan Pendapat Anak Dalam Pendidikan Islam Bagi Orang Tua Muslim Perpektif Al-quran Di Era Digital - Bainar Bainar (LPPM STAI Diniyah Pekanbaru, 2020)
Every person has a period and every era has a person, this is the right term we might say in Islamic education so that parents or educators can realize that education needs to keep up with the times that exist between these generations, not impose their will and not ignore children's opinions. Everything needs to be discussed. Every child's age must experience stages in the development of both affective, cognitive, and physics motor in their life, one of which is the development of religious values. The modernization of the times has an impact on decreasing awareness of the importance of religious values ​​for children in the digital era, habituation is needed from an early age in the parents' family as teachers. Listening to children's opinions with full consideration to make decisions in the world of Islamic education is very important for parents to be able to understand their needs, complaints according to the times they are facing so that they are full of confidence in their future. If parents do not listen to their children, the child's development will be influenced by digital in choosing their view of life so that parents will regret it forever. This research was conducted to find out how important it is to implement deliberation to achieve the goals of Islamic education.